A combined morphological, ultrastructural, molecular, and biochemical study of the peculiar family Gomontiellaceae (Oscillatoriales) reveals a new cylindrospermopsin‐producing clade of cyanobacteria. Issue 6 (16th November 2015) - Bohunická, Markéta; Mareš, Jan; Hrouzek, Pavel; Urajová, Petra; Lukeš, Martin; Šmarda, Jan; Komárek, Jiří; Gaysina, Lira A.; Strunecký, Otakar
Abstract : Members of the morphologically unusual cyanobacterial family Gomontiellaceae were studied using a polyphasic approach. Cultured strains of Hormoscilla pringsheimii, Starria zimbabweënsis, Crinalium magnum, and Crinalium epipsammum were thoroughly examined, and the type specimen of the family, Gomontiella subtubulosa, was investigated. The results of morphological observations using both light microscopy and transmission electron microscopy were consistent with previous reports and provided evidence for the unique morphological and ultrastructural traits of this family. Analysis of the 16S rRNA gene confirmed the monophyletic origin of non‐marine repre‐sentatives of genera traditionally classified into this family. The family was phylogenetically placed among other groups of filamentous cyanobacterial taxa. The presence of cellulose in the cell wall was analyzed and confirmed in all cultured Gomontiellaceae members using Fourier transform infrared spectroscopy and fluorescence microscopy. Evaluation of toxins produced by the studied strains revealed the hepatotoxin cylindrospermopsin (CYN) in available strains of the genus Hormoscilla . Production of this compound in both Hormoscilla strains was detected using high‐performance liquid chromatography in tandem with high resolution mass spectrometry and confirmed by positive PCR amplification of the cyrJ gene from the CYN biosynthetic cluster. To our knowledge, this is the first report of CYN production by soil cyanobacteria, establishing a previously unreported CYN‐producing lineage. This study indicates that cyanobacteria of the family Gomontiellaceae form a separate but coherent cluster defined by numerous intriguing morphological, ultrastructural, and biochemical features, and exhibiting a toxic potential worthy of further investigation.